Arab Republic of Egypt : First Review Under the Stand-By Arrangement and Monetary Policy Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2021)
The growth impact of the COVID-19 crisis has so far been less severe than expected, as strong consumption helped offset weak tourism and investment. Measures taken to address the health and social needs and support the sectors most directly affected by the crisis appear to have helped mitigate the impact of the shock. External market conditions have improved with a strong return of portfolio inflows since the approval of the Stand-By Arrangement (SBA).